PENERAPAN MODEL PROJECT BASED LEARNING PADA MATERI SIKLUS AIR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Inda Assaidah; Nurkholis; Rinto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the results of the analysis of observations in class V SD Negeri Babakanjati which shows the condition of low student learning outcomes accompanied by a lack of variation in using project-based learning models on the water cycle material. Referring to these problems, this study aims to determine student learning outcomes through the application of modelsProject Based Learning on water cycle material in class V Elementary School.Subject this study is a class studentV even semester of the 2022/2023 Academic Year, with a total of 19 students consisting of 11 female students and 8 male students.The research results show that application of modelsProject Based Learning can improve the learning outcomes of fifth grade elementary school students on the water cycle material. This matter it can be seen from the results of student mastery in cycle I by 21% with the category "Very Low" experiencing an increase of 63% in cycle II. Then the completeness of student learning outcomes in cycle 2 becomes 84% ​​in the "High" category. So it can be concluded that application of modelsProject Based Learning can improve the learning outcomes of fifth grade elementary school students on the water cycle material. The results of this study are expected to help teachers in make use of models Project Based Learning as an effort to improve student learning outcomes and can be used as an option in implementing meaningful learning by applying various models and innovative learning methods. Keywords: Class Action Research, Project Based Learning, Student Learning Outcomes